Appearance of L90I and N205S Mutations in Effector Domain of NS1 Gene of pdm (09) H1N1 Virus from India during 2009–2013. (15th September 2014) - Kumar, Sachin; Khare, Shashi; Saidullah, Bano; Gandhoke, Inderjeet; Ram, Hanu; Singh, Supriya; Chauhan, L. S.; Rai, Arvind
Abstract : In the present study, full length sequencing of NS gene was done in 91 samples which were obtained from patients over the time period of five years from 2009 to 2013. The sequencing of NS gene was undertaken in order to determine the changes/mutations taking place in the NS gene of A H1N1 pdm (09) since its emergence in 2009. Analysis has shown that the majority of samples belong to New York (G1 type) strain with valine at position 123. Effector domain of NS1 protein displays the appearance of three mutations L90I, I123V, and N205S in almost all the samples from 2010 onwards. Phylogenetic analysis of available NS1 sequences from India has grouped all the sequences into four clusters with mean genetic distance ranging from 12% to 24% between the clusters. Variability in length of NS1 protein was seen in sequences from these clusters, 230-amino-acid-residue NS1 for all strains from year 2007 to 2008 and for 21 strains from year 2009 and 219-residue products for 37 strains from year 2009 and all strains from year 2010 to 2013. Mutations like K62R, K131Q, L147R, and A202P were observed for the first time in NS1 protein and their function remains to be determined.